Functional Model of Supply Chain Waste Reduction and Control Strategies for Retailers—The USA Retail Industry - Victory Ikpe; Mohammad Shamsuddoha (Logistics)
Background: The US retail sector grapples with persistent challenges related to supply chain waste, including inefficiencies, overstocking, and logistical barriers, necessitating targeted reduction strategies to mitigate escalating costs, environmental impacts, and diminished profitability. Methods: This study adopts a qualitative research method that draws on secondary data sources such as books, journals, articles, and websites to explore supply chain waste reduction strategies within the US retail industry. The study delineates various supply chain waste types, examines associated challenges and drivers, and proposes a simplified model tailored to the US retail landscape to enhance efficiency and sustainability through waste reduction and control. Results: The findings of this paper underscore the necessity for proactive measures within the US retail sector to minimize supply chain waste, optimize operations, and bolster environmental stewardship. Conclusions: By offering a comprehensive overview actionable insights and proposed reverse logistics model, this study aims to equip US retailers with strategies conducive to sustainable growth and heightened competitiveness while advancing the broader discourse on supply chain efficiency and waste reduction.